Genome-centric view of the microbiome in a new deep-sea glass sponge species Bathydorus sp. - Wei, Tao-Shu; Gao, Zhao-Ming; Gong, Lin; Li, Qing-Mei; Zhou, Ying-Li; Chen, Hua-Guan; He, Li-Sheng; Wang, Yong (Frontiers in Microbiology, 2023)
Abstract Sponges are widely distributed in the global ocean and harbor diverse symbiotic microbes with mutualistic relationships. However, sponge symbionts in the deep sea remain poorly studied at the genome level. Here, we report a new glass sponge species in the genus Bathydorus and provide a genome-centric view of its microbiome. We obtained 14 high-quality prokaryotic metagenome-assembled genomes (MAGs) affiliated with the phyla Nitrososphaerota, Pseudomonadota, Nitrospirota, Bdellovibrionota, SAR324, Bacteroidota, and Patescibacteria. Thirteen of these MAGs probably represent new species, suggesting high novelty of the deep-sea glass sponge microbiome. An ammonia-oxidizing Nitrososphaerota MAG B01 that accounted for up to 70% of the metagenome reads dominated the sponge microbiomes. The B01 genome had a highly complex CRISPR array, which likely represents an advantageous evolution towards a symbiotic lifestyle and forceful ability to defend against phages. A sulfur-oxidizing Gammaproteobacteria species was the second most dominant symbiont, and a nitrite-oxidizing Nitrospirota species could also be detected but with lower relative abundance. Bdellovibrio species represented by two MAGs B11 and B12, were firstly reported as potential predatory symbionts in deep-sea glass sponges and have undergone dramatic genome reduction. Comprehensive functional analysis indicated that most of the sponge symbionts encoded CRISPR-Cas systems and eukaryotic-like proteins for symbiotic interactions with the host. Metabolic reconstruction further illustrated their essential roles in carbon, nitrogen and sulfur cycles. Besides, diverse putative phages were identified from the sponge metagenomes. Our study expands knowledge of microbial diversity, evolutionary adaption, and metabolic complementarity in deep-sea glass sponges.